Detuned Resonant Capacitors Selection for Improved Misalignment Tolerance of LCC-S Compensated Wireless Power Transfer System - Weijie Li; Weiyao Mei; Quan Yuan; Yongfeng Song; Zhonghao Dongye; Lijun Diao (IEEE Access, 2022)
This study proposes a detuned resonant capacitor selection strategy to eliminate the influence of the changed coupling coefficient on the transferred power and efficiency of a wireless power transfer (WPT) system using the LCC-S resonant topology. The output characteristics of the conventional tuned LCC-S system and the novel detuned system are analyzed and compared in detail, the different effects of the detuned parameters on the system output performance are expounded by simulations, and an optimal detuned parameter design process is presented. By adjusting the compensated capacitors on the transmitting side, the output voltage can be constant under varying coupling conditions without changing the switching frequency. Experiments with a 1.5kW power scale were conducted to verify the proposed theoretical analysis. The results show that the fluctuation of the output voltage is restricted to 8.2% in the optimized system when the coupling coefficient changes from 0.18 to 0.38. Under the rated coupling conditions, the experimental results demonstrate that compared with ZPA (88.29%) and ZVS (90.66%), ZCS (91.52%) operating conditions are more suitable for a WPT system equipped with IGBTs to improve the overall efficiency.